INTERNALISASI NILAI-NILAI MODERASI BERAGAMA TERHADAP SISWA SMKN 6 KOTA JAMBI TAHUN PELAJARAN 2024/2025 - Ida Riyanty; Sya’roni; Jannah, Riyadul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to: 1. Describe students' understanding related to the internalization of religious moderation values at SMKN 6 Kota Jambi; 2. Describe the strategy in the implementation of internalization of religious moderation values at SMKN 6 Kota Jambi; 3. Describe the impact caused by the internalization of religious moderation values on student attitudes, mindsets, and behaviors at SMKN 6 Kota Jambi. The type of research used in this study is qualitative research. The data collection technique of this research uses observation, interviews, documentation, and field notes. The results of the research are: 1. The internalization of religious moderation values at SMKN 6 Jambi City has been carried out optimally and maximally. This is because the students have been able to receive instruction from teachers to instill in them the values of religious moderation; 2. The internalization of religious moderation values is a pedagogical process that can be implemented through various models, in particular: a. Through Viral Case Analysis and Lectures, Friday Pulpit on the Concept of Moderation; b. Through Material Integration in KBM Activities; c. Assessing Students' Knowledge; d. Contemplation of the Knowledge Obtained; 3. The internalization of religious moderation values in character development positively affects attitudes, mindsets, and social behaviors rooted in character values that develop in the environment of SMKN 6 Jambi City, including: a. The importance of integrity; b. Students' openness to thought; and c. Tolerance.